BREATHING EXERCISE SAMA BAIKNYA DALAM MENINGKATKAN KAPASITAS VITAL (KV) DAN VOLUME EKSPIRASI PAKSA DETIK PERTAMA (VEP1) PADA TENAGA SORTASI YANG MENGALAMI GANGGUAN PARU DI PABRIK TEH PT. CANDI LOKA JAMUS NGAWI - Imania, Dika Rizki; Tirtayasa, Ketut; Indra Lesmana, Syahmirza (Sport and Fitness Journal, 2015)
Impaired lung function is a disease caused by various reasons, such as viruses, bacteria, dustan do ther particles. It is exposure by dust tea every day of lab or sorting result in decrease of lung function. This study aims to determine the role of breathing exercise in improving forced expiratory volume in 1 second (FEV1) and vital capacity (VC). The research designs is experiment trueby the one grouppre-testandpost-test design, where taking sample from the population by random that ful fill the inclusion and exclusion criteria. There are 10 groups of people and getting treatment Breathing Exercise. Frequency of exercise 3 times a week for 6 weeks. The subjects were all lab or ssorting who had impaired lung that has been diagnosed by the measured procedure with lung physiology measure ments were performed using aspirometer in the tea factory of PT. Candi Loka Jamus Ngawi. The significance analysis of Pairedt-test (paired) showed that giving breathing exercise increase the vital capasity (VC) and forced expiratory volume (FEV1) was significantly different (p <0.05). While different teston VC and FEV1 after treatment with the Independentt-test (unpaired) show that the value of p =0.749. The results means that there isno an increase between the value of forced expiratory volume in 1 second (FEV1) and Vital Capacity (VC) after treatment. Thus it can be concluded, the giving of breathing exercises is as better as to increase the value offorced expiratory volumein 1 second (FEV1) and Vital Capacity (VC).
Keywords: Breathing exercises, Forced expiratory volumein 1 second (FEV1) and Vital Capacity (VC).